Single-cell analysis reveals prognostic fibroblast subpopulations linked to molecular and immunological subtypes of lung cancer - Christopher J. Hanley; Sara Waise; Matthew J. Ellis; Maria A. Lopez; Wai Y. Pun; Julian Taylor; Rachel Parker; Lucy M. Kimbley; Serena J. Chee; Emily C. Shaw; Jonathan West; Aiman Alzetani; et al. (Nature Communications, 2023)
Fibroblast heterogeneity is a prominent but poorly understood feature of solid tumours. Here three major fibroblast subpopulations in non-small cell lung cancer are identified and characterised through single cell RNA-sequencing, multiplexed immunohistochemistry and digital cytometry.